AB0456 Improvement and maintenance of hemoglobin levels among rheumatoid arthritis, psoriatic arthritis & ankylosing spondylitis patients with anemia of inflammation after treatment with golimumab: 3 yr pooled analysis from golimumab rheumatology clinical program. (23rd January 2014) - Furst, D.E.; Gathany, T.A.; Kay, J.; Wasko, M.C.; Keystone, E.; Kavanaugh, A.; Deodhar, A.; Murphy, F.; Han, C.; Doyle, M.K.
Abstract : Objectives: The purpose of this analysis was to determine the long-term effects of golimumab (GLM) on anemia of inflammation (AOI) in patients (pts) with RA, PsA, and AS. Methods: Data through 3 yrs were pooled from 5 studies in the GLM rheumatology clinical program including: 3 RA studies (GO-BEFORE, GO-FORWARD, GO-AFTER), 1 PsA study (GO-REVEAL), and 1 AS study (GO-RAISE). SC placebo (PBO) or GLM (50mg or 100mg) was administered q4wks in the randomized portions of the ongoing Ph3 trials. At 6 months/1 yr, pts remaining in the studies entered long term extensions (LTE) and received GLM 50mg or 100mg q4wks in an unblinded fashion. Dose escalation from 50mg to 100mg was allowed; no dose reduction was permitted.Primary endpoints compared pts treated with GLM±MTX with pts receiving placebo (PBO±MTX). Pts were defined as anemic if their hemoglobin (Hgb) were below the age- and sex-specific normal range of the central laboratory (Quintiles Laboratories, Smyrna, GA, United States). Normal Hgb for the central laboratory was 11.6 to 16.2 g/dL for women aged ≤65 yrs, 11.0 to 16.1 g/dL for women aged ≥66 yrs, 13.0 to 17.5 g/dL for men aged ≤65 yrs, and 12.6 to 17.7 g/dL for men aged ≥66 yrs. A subset of pts with AOI (anemic and ferritin ≥60 ng/mL), at baseline (BL) was analyzed for normalization and improvement of Hgb levels at 6 months; the long-term maintenance of these improvements were analyzed at yrs 1, 2, and 3. Results: At 6 months, among pts who had AOI at BL, pts treated with GLM±MTX showed greater Hgb improvements vs pts treated with PBO±MTX (median improvement: 1.45 g/dL vs 0.55 g/dL, p<0.001) at 6 months. More GLM±MTX-treated pts achieved normal Hgb (67.9% vs 42.3%, p=0.020). 93.0% to 96.7% of these pts maintained normal Hgb at 1-, 2- and 3yrs(Table). Conclusions: Among pts with RA, PsA and AS with AOI at BL, pts treated with GLM±MTX achieved greater median improvements in Hgb and greater proportions had normalized Hgb levels at 6 months. Pts who achieved normal levels at 6 months and continued treatment with GLM, maintained the normal Hgb levels through 3 yrs. These improvements in AOI support the hypothesis that AOI responds to suppression of inflammation with GLM. Disclosure of Interest: D. Furst Grant/Research support from: Investigators for Janssen Research & Development, LLC sponsored clinical study, T. Gathany Employee of: Janssen Global Service, LLC, J. Kay Grant/Research support from: Investigators for Janssen Research & Development, LLC sponsored clinical study, M. Wasko Grant/Research support from: Investigators for Janssen Research & Development, LLC sponsored clinical study, E. Keystone Grant/Research support from: Investigators for Janssen Research & Development, LLC sponsored clinical study, A. Kavanaugh Grant/Research support from: Investigators for Janssen Research & Development, LLC sponsored clinical study, A. Deodhar Grant/Research support from: Investigators for Janssen Research & Development, LLC sponsored clinical study, F. Murphy Grant/Research support from: Investigators for Janssen Research & Development, LLC sponsored clinical study, C. Han Employee of: Janssen Global Service, LLC, M. Doyle Employee of: Janssen Research & Development, LLC